Comparative analysis assessing the effectiveness and efficiency of paper-based Vs digital approaches in Kadoma cholera case area targeted interventions between june to august 2024. A cross-sectional study. - Banda, Precious Sabina; Ali, Anahita (Student's Journal of Health Research Africa, 2025)
Study Aim To assess the effectiveness and efficiency of paper-based vs digital approaches in the Kadoma cholera case area, targeted interventions between June to August 2024. Methodology A field trial was employed to compare paper-based and digital data collection methods during Case Area Targeted Interventions (CATIs) within the context of the cholera outbreak. Twenty CATI team members were randomly assigned to two groups using a random number generation process. Results The data reveal a fairly balanced gender distribution among the 20 implementors: 11 males and 9 females. The collection process uses paper-based and digital methods. There were 140 (98%) completed interviews using the paper-based method and 142 (100%) using the digital method. The number of completed interviews using the two approaches does not differ significantly (p-value < 0.05). The paper-based mean is 12 minutes (SD =2.89, CI 11.53 -12.47), the digital mean is 9 minutes (SD =2.85, CI 9.53 - 10.47), and the t-test for the mean difference is 7.502. The p-value was 0.0001. The digital method demonstrated slightly higher completion rates (100%) compared to the paper-based method (98%). Conclusion The study demonstrates that digital methods outperform paper-based approaches in terms of efficiency, resulting in considerable time savings during data collection. While both methods achieved high completion rates, the digital approach allows for faster data capture and swifter public health responses, which are crucial during outbreaks. Recommendations Kadoma City Council should prioritize the adoption of digital methods for time-sensitive situations, particularly during outbreak investigations where a swift response is crucial.